Psychosocial and Emotional Factors Influencing the Choice between Cesarean Section and Natural Birth - Syed Qasim Shah, Mahmood Ali Khan Jafri, Fizza Ashfaq, Aisha Taj, Shah Muhammad Khan, Hamidullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The choice between cesarean section and natural birth is influenced by a complex interplay of psychosocial and emotional factors. While medical indications play a crucial role, non-medical reasons such as fear, anxiety, social influence, and personal preferences also impact the decision-making process. Understanding these factors is essential for improving maternal care and ensuring informed choices. Methods: The current research was conducted at Mardan Medical Complex Mardan from January 2023 to June 2023. This study aimed to explore psychosocial and emotional influences on birth mode selection among pregnant women in their third trimester who had already decided on their mode of delivery. A total of 323 participants were selected using a systematic sampling method to ensure adequate representation. Inclusion criteria focused on pregnant women aged 18 years or older who provided informed consent, while those with high-risk pregnancies requiring mandatory cesarean sections or with a history of psychiatric disorders were excluded. Data collection involved structured questionnaires assessing demographic details, psychosocial influences, and emotional responses, supplemented by semi-structured interviews with 50 participants for an in-depth exploration. A pilot study was conducted to ensure the reliability and validity of the instruments. Results: Sociodemographic factors significantly influenced delivery preferences, with older and less-educated women more likely to opt for cesarean sections. Partner support was associated with a preference for vaginal birth, while family pressure and cultural beliefs contributed to cesarean selection. Emotional factors such as fear of labor pain, high anxiety levels, and lack of confidence in natural birth were strong predictors of cesarean preference. Logistic regression identified fear of pain as the most influential factor (OR = 5.1, p < 0.001), followed by family pressure (OR = 2.8, p < 0.001) and high anxiety levels (OR = 3.5, p < 0.001). Conclusion: The findings underscore the significant role of psychosocial and emotional factors in shaping childbirth decisions. Addressing psychological concerns through prenatal education and unbiased counseling can empower women to make informed choices. Integrating these considerations into maternity care can enhance maternal satisfaction, reduce anxiety, and improve overall birth experiences. Healthcare providers should adopt a patient-centered approach that acknowledges the emotional and social dimensions of childbirth decisions. Providing comprehensive education on birth options, addressing fears, and ensuring supportive environments can lead to more positive maternal outcomes and reduce unnecessary cesarean sections driven by non-medical factors. Keywords: Cesarean section, Vaginal birth, Psychosocial factors, Emotional influence, Fear of childbirth, Maternal decision-making